Amine or Azo functionalized hypercrosslinked polymers for highly efficient CO2 capture and selective CO2 capture. (June 2021) - Qiao, Yuanting; Zhan, Zhen; Yang, Yuwan; Liu, Manying; Huang, Qi; Tan, Bien; Ke, Xuebin; Wu, Chunfei
Graphical abstract: Abstract: Hypercrosslinked polymers (HCPs) are very promising for large-scale applications due to their easy preparation, high thermal stability, and good capability of CO2 capture. Currently, many amine-functionalized porous materials are prepared through two steps. In this paper, the amine-functionalized HCPs was obtained with a one-step method and it showed a high CO2 adsorption up to 4.24 mmol/g at 273.15 K. In addition, since the azo-functionalized porous materials have many potential applications like the photoresponsive 'smart' materials, azobenzene is an attracting functional group for the development of porous materials. Herein, the azo-functionalized HCPs is firstly reported, and it is used as CO2 adsorbents (3.02 mmol/g at 273.15 K) performing good CO2 /N2 selectivity (34.52 at 298.15 K).